Enhancing space resilience through non-materiel means - McLeod, Gary, 1948- (Research report (Rand Corporation) ;, 2016)
"Space is now a congested, contested, and competitive environment. Space systems must become more resilient to potential adversary actions and system failures, but changes to space systems are costly. To provide a complete look at resilience and possibly realize some benefit at lower cost, the Air Force asked RAND to identify non-materiel means--doctrine, organization, training, leadership and education, personnel, facilities, and policy--to enhance space resilience over the near and far terms. The authors developed implementation options to improve resilience based on a notional space protection operational concept: enhancing the capability of space operators to respond, in a timely and effective manner, to adversary counterspace actions. Operators need actionable information, appropriate organization and tactics, and dynamic command and control, supported by appropriate tools and decision aids, relevant training and exercises, and qualified personnel brought into the career field. The authors also recommend that Air Force Space Command develop a formal, end-to-end, space protection concept of operations (CONOPS) that captures all elements needed to improve resilience. In addition, the CONOPS could potentially follow the tenet of centralized control and decentralized execution in certain situations, such as when responding to adversary counterspace actions. For the near-term options, the rough order of magnitude (ROM) nonrecurring engineering (NRE) cost of implementation is estimated to be between $2.5 million and $3.6 million. For the far-term options, the ROM NRE cost is estimated to be between $109 million and $166 million, with the ROM recurring cost between $4 million and $5.4 million per year"--Publisher's description